Validation and Optimization of Ultrasound-Assisted Dispersive Liquid-Liquid Microextraction as a Preparation Method for Detection of Methadone in Saliva with Gas Chromatography-Mass Spectrometry Technique - Ahmad Shekari; Mehdi Forouzesh; Roohollah Valipour; Fardin Fallah; Pardis Shojaei (Tabriz University of Medical Sciences, 2020)
Purpose: We investigated validation and optimization of ultrasound-assisted dispersive liquidliquid microextraction (UADLLME) as a preparation method for detection of methadone in saliva samples. Methods: We used blank and methadone-containing saliva samples and also standard methadone solution. Sodium hydroxide and chloroform were added to samples and they were held in ultrasonic bath. Then preparations were centrifuged and extracted analyte was analyzed by gas chromatography-mass spectrometry (GC-MS). Accuracy was measured by Intra and between-day mean relative errors (RE). Precision was assessed by coefficient of variation (CV). Recovery, specificity, linearity and limits of detection and quantification were also determined. Optimization was conducted for ultrasound duration, pH and extraction phase volume. Efficiency of dispersive liquid-liquid microextraction (DLLME) and UADLLME were compared. Results: Intra and between-day accuracies (2.3 -7.5%), recovery (89.4-115.5%) and precision (5.2-11.3%) were all acceptable. Calibration curve was linear in the concentration range of 150 ng/mL-10 µL/mL with R2 >0.9995 and equation of y=86.901x-5342.5. Limits of detection and quantification were 50 and 150 ng/mL, respectively. Specificity was measured by comparing retention times of saliva samples (containing methadone metabolites and other commonly used drugs) during UADLLME/GC-MS analysis and no interference was observed. Recovery of UADLLME was 1.4 of DLLME. Solvent and sample volumes required for UADLLME were 1/200 and 1/20 of DLLME. The greatest efficiency obtained at pH of 10, with ultrasound treatment duration of 5 minutes and extraction phase volume of 1000 µL. Conclusion: Study found that UADLLME/GC-MS is a valid and efficient method for detection of methadone in oral fluid.